Research of the method of increasing the object determination accuracy on the low-resolution video stream - Barsov, Valeriy; Kosterna, Olena; Plakhotnyi, Oleksandr (Національний технічний університет "Харківський політехнічний інститут", 2021)
Study subject. The article proposes and investigates a method for increasing the accuracy of determination of the distance and the obstacle geometric parameters based on object contours determination using a computer vision system that uses low-resolution sensors. The goal is the effectiveness evaluation of the proposed method. Tasks: to conduct experimental researches of the quality indicators of the method of increasing the object contours determination accuracy; evaluate the effectiveness of this method. Used methods: statistical modeling, laboratory scale tests. The obtained results: the analysis of the proposed method efficiency was carried out and the influence of this method on the determination accuracy of the distance and object geometric parameters was evaluated. Conclusions: the considered method made it possible to achieve the increasing the determination accuracy of the distance and geometric object parameters by compensating for image blur using the Lucy-Richardson deconvolution algorithm. The obtained data showed a decrease in the maximum error in determining the distance from 8% to 4% and the error in the geometric object parameters from 7.7% to 5.8%. The implementation of this approach was carried out in the Python programming language.

Предмет вивчення. У статті пропонується і досліджується метод підвищення точності визначення відстані і геометричних параметрів перешкоди на основі визначення контурів об'єкта за допомогою системи технічного зору з використанням датчиків низькою роздільною здатністю. Метою є оцінка ефективності запропонованого методу. Завдання: провести експериментальні дослідження, показників якості методу підвищення точності визначення контурів об'єкта; оцінити ефективність роботи даного методу. Використовувані методи: статистичне моделювання, лабораторні натурні випробування. Отримані результати: проведено аналіз ефективності роботи запропонованого методу і оцінено вплив даного методу на точність визначення відстані і геометричних параметрів об'єкта. Висновки: Розглянутий метод дозволив отримати підвищення точності визначення відстані і геометричних параметрів об'єкта шляхом компенсації розмиття зображення, за допомогою алгоритму деконвуляціі Люсі-Річардсона. Отримані дані показали зниження максимальної помилки визначення відстані з 8 до 4% і помилки геометричних параметрів об'єкта з 7,7 до 5,8%. Реалізація даного підходу виконувалася на мові програмування Python.
Дослідження методу підвищення точності визначення об'єкта на відеопотоці низької роздільної здатності
Keywords: stereoscopic vision systems; distance determination; geometric parameters determination; monocular vision systems; стереоскопічні системи технічного зору; визначення відстані; визначення геометричних параметрів; бінокулярні системи технічного зору